Priority driven Call Scheduling in Mobile Networks: A MOGA based approach - Thakurta, Parag Kumar Guha (2015)
Enhanced mobile communication in current days demands a drastic evolution in resource management strategies to meet the quality of service (QoS) requirements for the network. Call scheduling is such an important scheme for efficient utilization in spite of scarcity of resources. In this paper, a priority driven call scheduling technique is proposed for efficient routing in mobile networks. The proposed scheduler is addressed with two conflicting objectives: to minimize the mean routing cost, and to achieve uniformity in the overall system utilization. In this context, a Multi Objective Genetic algorithm (MOGA) based approach is introduced for finding an optimal route from several alternatives pertaining to the network constraints. This results in effective scheduling and simultaneous improvement in call acceptance for the system. The proposed model takes into account the significance of priority in a comprehensive manner. The performance of the proposed model is evaluated in network scenarios with different parameters and service requirements. In addition, results from simulation studies show the quality of approximation obtained by the proposed model.